AWARENESS PROCESS OF THE PARTY AND REAL SITUATION OF EDUCATION AND TRAINING IN VIETNAM OVER 35 YEARS OF INNOVATION (1986-2021) (International Conference on Social and Islamic Studies, 2021)
Education and training play an extremely important role for any country, nation. Being aware of position, role of education and training in the development of the country, during innovation in Vietnam, the Vietnamese Communist Party always pays attention to leadership, direction of this important field. In this writing, the author analyzes to clarify the theory awareness process of the Party of education and training; generalizes real situation of education and training in Vietnam over 35 years of innovation from 1986 to2021 under perspective of the Party.